2002
DOI: 10.1161/hs0302.104110
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hemorrhagic Transformation in Patients Receiving Intra-Arterial Thrombolysis

Abstract: Background and Purpose-Hemorrhagic transformation (HT) is a major complication of intra-arterial (IA) thrombolytic therapy. Identifying significant predictors of hemorrhage after thrombolysis would be useful in guiding patient selection for IA treatment. Methods-Data were collected retrospectively on consecutive patients with acute focal cerebral ischemia within the anterior or posterior circulation who were treated with combined intravenous (IV)-IA or pure IA thrombolysis over an 8-year period at the UCLA Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(133 citation statements)
references
References 30 publications
(12 reference statements)
14
116
1
2
Order By: Relevance
“…Although there are many studies that report various clinical and molecular variables predictive of HT, 30,31 imaging BBB permeability is an intuitive and conceptually attractive method to assess for HT risks. Abnormal BBB permeability can be seen qualitatively as parenchymal enhancement in conventional delayed postgadolinium enhanced MR imaging, with enhancement in the early period of AIS being predictive of HT.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies that report various clinical and molecular variables predictive of HT, 30,31 imaging BBB permeability is an intuitive and conceptually attractive method to assess for HT risks. Abnormal BBB permeability can be seen qualitatively as parenchymal enhancement in conventional delayed postgadolinium enhanced MR imaging, with enhancement in the early period of AIS being predictive of HT.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic transformation (HT) is a common complication of intra-arterial thrombolysis for the treatment of acute ischemic stroke, with an estimated incidence rate of 18-71% [1,2] , depending on factors such as the thrombolytic agent used and the route of administration [1,3,4] . Recent studies showed that different s ubtypes of HT may have a different prognosis, some having a higher recanalization rate and better outcome [5] ,while some are associated with very poor clinical outcomes [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Intra-arterial thrombolytic therapy is increasingly used at many large institutions for treatment of acute ischemic stroke. [2][3][4][5] Recently, on the basis of results of the Prolyse in Acute Cerebral Thromboembolism (PROACT) II investigation, 5 the American Society of Interventional and Therapeutic Neuroradiology stated that intra-arterial thrombolytic therapy could be considered acceptable and appropriate for acute stroke in selected patients. 6 Hemorrhagic transformation with deterioration of neurological symptoms is the major complication of intra-arterial thrombolytic therapy; a frequency between 10% and 15.4% has been observed.…”
mentioning
confidence: 99%